Measurement and modeling of solubilities of flurbiprofen in modified supercritical carbon dioxide. - Chin, Gui Jin. (2009)
Supercritical fluids refer to substances which are at or above their critical temperature and pressure. Supercritical fluid technology has gained popularity over the years in various industries and carbon dioxide (CO2) is a preferred choice for solvent as it is non-toxic, inflammable and has a convenient critical point. Several processes using supercritical fluids also employ an organic modifier in order to enhance the solubility of the solute. The knowledge of solubility of solutes in CO2 is important for the design of processes such as supercritical extraction and supercritical fluid chromatography. The drug of interest in this project is flurbiprofen which is a type of non steroid anti-inflammatory drug administered to patients suffering from pain and inflammation. As flurbiprofen is a large polar compound, it has limited solubility in supercritical CO2, thus modifiers such as methanol are added to increase the polarity of the CO2 so as to increase solubility. The solubility of flurbiprofen in methanol-modified supercritical CO2 was investigated at 30.0 °C and 40.0 °C at pressure ranging from 90 to 245 bar using the Phase Monitor. A protocol for the experiment that avoids technical difficulties when using the Phase Monitor has been developed. The results of solubility in methanol-modified supercritical CO2 were modeled using the Peng-Robinson equation of state with 1-parameter van der Waals mixing rules. The absolute average relative deviations range from 6.80% and 14.61%.